2013
DOI: 10.1080/00981389.2013.780835
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Experience of Their Child's First Psychiatric Breakdown: “Welcome to Hell”

Abstract: Clinicians and researchers have emphasized the importance of helping the primary caregivers of persons going through the first outbreak of psychiatric illness in order to mitigate the negative consequences of the illness on the patient and the caregivers. The aim of the current qualitative, retrospective study is to examine the experiences, challenges, and difficulties faced by Israeli parents during the outbreak of psychiatric illness in their children. In-depth, semi-structured interviews were conducted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
10
0
3
Order By: Relevance
“…Although one study showed that most of the participating parents endorsed biological or life events as causes [41], other studies showed that parents blamed themselves for causing their child’s disorder [40, 44] and perceived themselves as “bad parents” [45]. The onset of the illness was perceived as sudden and traumatic and as changing the cognitive schema of the child from a “normal child” to other representations [46]. A mental illness, in comparison to a physical illness, was shown to be perceived by the parent as more devastating, unexpected, chronic, stigmatizing, and leading to the loss of the patient’s organic personality [43].…”
Section: Resultsmentioning
confidence: 99%
“…Although one study showed that most of the participating parents endorsed biological or life events as causes [41], other studies showed that parents blamed themselves for causing their child’s disorder [40, 44] and perceived themselves as “bad parents” [45]. The onset of the illness was perceived as sudden and traumatic and as changing the cognitive schema of the child from a “normal child” to other representations [46]. A mental illness, in comparison to a physical illness, was shown to be perceived by the parent as more devastating, unexpected, chronic, stigmatizing, and leading to the loss of the patient’s organic personality [43].…”
Section: Resultsmentioning
confidence: 99%
“…Estudios anteriores señalan que las crisis de salud mental no afectan a individuos aislados, se sufren en el interior de las familias y afectan a todos los que conviven con la persona enferma22, 23, 24. El presente trabajo revela que los cuidadores participan en las crisis, asumen el protagonismo de enfrentarlas priorizando mantener el vínculo afectivo y esto sin duda transforma la vida familiar.…”
Section: Discussionunclassified
“…Diesen Konflikt bewältigen sie meist alleine, da sie aufgrund von Scham und Schuldgefühlen mit Personen außerhalb der Familie wenig über eine psychische Erkrankung sprechen [11]. Betroffene Eltern empfinden nicht selten eine Macht-und Hilflosigkeit durch mangelnde Unterstützung der Gesundheitsbehörden, Schuldgefühle, Wut und Isolation, begleitet von einem tiefen Gefühl des Verlustes und Trauer [12] Ausschlusskriterien waren schwere somatisch-internistische und psychische Erkrankungen (z. B.organische Erkrankung des Gehirns) sowie das Nichtvorliegen der Einverständniserklärungen. Eine vorbestehende Medikation bei den Patienten stellte kein Ausschlusskriterium dar.…”
Section: Introductionunclassified